Critical Performance Assessment of Precast Concrete Quality in High-Rise Buildings Compliance with National Standards - Muhammad Hunsan; Erny; Erniati Bachtiar; Arman Setiawan; Rita Hardianti Aris (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
This study critically assesses Precast Concrete (PC) quality compliance in Indonesian high-rise buildings by comparing material strength, geometric tolerances, and seismic connection performance against SNI requirements. Using five years of official inspection data (2020–2025) from 120 certified lots (BSN/PUPR), the analysis identifies recurring non-compliance, including a 15.0% compressive strength defect rate, 8.5% AOQ, and 17.1% reinforcement cover deficiencies that may compromise structural durability. Wet joints exhibit better seismic resilience (μ = 4.5) than dry joints (μ = 3.8), though dry joints show pinching effects that reduce energy dissipation.Key root causes include moisture instability, admixture dosing errors, and precision gaps, revealing a persistent mismatch between documented procedures and actual statistical quality control. The study recommends implementing automated QC systems and strengthening SNI certification through more rigorous statistical approaches. Future work should integrate machine-learning predictive models using real-time factory data to enhance defect prevention.